2020
DOI: 10.1111/andr.12895
|View full text |Cite
|
Sign up to set email alerts
|

Effects of platelet‐rich plasma on spermatogenesis and hormone production in an experimental testicular torsion model

Abstract: Background Platelet‐rich plasma is a biological instrument rich in growth factors and cytokines. Objectives The aim of this study was to investigate the effect of platelet‐rich plasma on spermatogenesis and hormone production in an experimental testicular torsion model. Materials and methods The rats were randomly divided into three groups, including six rats in each group as follows: the first group as the sham group; the second group as the ischemia/reperfusion + Saline group and the third group as the ische… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…In another experimental study, Kutluhan et al showed that plateletrich plasma increases testosterone levels, further improving spermatogenesis. This beneficial effect is likely due to PRP's effect on Leydig cells' survival (Kutluhan et al, 2021). In our study, improvements in the sperm parameters, especially sperm count and viability, are due to the presence of various antioxidants, which affects the ability of Leydig cells for testosterone synthesis, leading to improved spermatogenesis.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…In another experimental study, Kutluhan et al showed that plateletrich plasma increases testosterone levels, further improving spermatogenesis. This beneficial effect is likely due to PRP's effect on Leydig cells' survival (Kutluhan et al, 2021). In our study, improvements in the sperm parameters, especially sperm count and viability, are due to the presence of various antioxidants, which affects the ability of Leydig cells for testosterone synthesis, leading to improved spermatogenesis.…”
Section: Discussionmentioning
confidence: 58%
“…In addition to various compounds, such as anti-inflammatory cytokines and enzymes with antioxidant properties, since various growth factors with high concentrations are present in CM and extracellular vesicles, their anti-apoptotic effect may be due to this mixture of growth factors. In a study on the effects of PRP on testicular ischaemia models, the reduced apoptosis was due to the high growth factors (Kutluhan et al, 2021).…”
Section: Many Studies Have Shown That the Immunosuppressive Activity Ofmentioning
confidence: 99%
“…In addition, they reported an elevated number of spermatogenic stem cells and testosterone levels in rat testis 10 . It was also reported that PRP improves reproductive hormone production, the state of oxidative stress, and antioxidant markers in testicular torsion 9,11 . Furthermore, the beneficial role of PRP in improving sperm parameters and sperm cryopreservation is reported in some studies 37,38 .…”
Section: Discussionmentioning
confidence: 94%
“…These growth factors are enclosed in the alpha‐granules of platelets, which release them by degranulation 10 . In this line, Kutluhan et al showed that PRP improved the spermatogenesis process and production of FSH and testosterone in rats following experimental testicular torsion 11 . Also, Angellee et al indicated that incubation of abnormal semen with PRP positively affected abnormal semen parameters 12 …”
Section: Introductionmentioning
confidence: 99%
“…PRP intracavernous injection stabilized the CXC chemokine receptor 2 (CXCR2) and increased the CXC motif chemokine ligand 5 (CXCL5) expression in the major pelvic ganglion after bilateral CN crush injury, thus enhancing neuroprotection (Wu et al, 2021). Furthermore, in rats with induced testicular torsion-detorsion (TD), PRP treatment significantly mitigated the produced degeneration, by improving testicular histoarchitecture, state of oxidative stress and antioxidant markers and modulating the expression of IL-1β, TNFα, and caspase-3 and increase the B-cell lymphoma 2 (BCL2) expression (Samy et al, 2020), and increasing FSH and testosterone levels (Kutluhan et al, 2021).…”
Section: Prp and Male Reproduc Tive Dys Fun C Tionmentioning
confidence: 99%